Public Facilities Preference of Youth Residents in Low-cost Housing Flats towards Sustainable Living - Sabrina Ismail, Alice; Shahida Azili, Nor; Ahmad @ Taufik, Fadhlina; Mohamad Esa, Ezlina; Azim Ashar, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Public facilities are an important component that guarantees the country’s growth and human development. Nonetheless, public facilities located in residential areas play an essential role in providing support services to create a viable and sustainable living for cohesive communities. Past studies on public facilities, however, have much focused on accessibility, provisioning, and service requirements. So far, there has been no literature that addresses the aspects of preparing and managing public facilities for the benefit of youth residents in low-cost housing flats. The objective of this study, therefore, is to obtain the perception of youth residents in two low-cost housing flats located in the urban areas of Kuala Lumpur and Johor Bahru city. This is vital to obtain youth resident satisfaction in terms of maintenance effectiveness on the provided public facilities. To conduct this study, qualitative and quantitative methods involving the perception of youth residents on two selected case studies were done to establish appropriate public facility design attributes. Findings indicate that proper preparation and management of public facilities may contribute to the development of positive psychological behavior among youths in terms of promoting the value of responsibilities (obligation) and respect (gratitude). The findings are of benefits for future designers, builders, developers, and related authorities to improve the preparation and management of public facilities in low-cost housing sectors. This is important to enhance the quality of public facilities for the youths in low-cost housing towards better satisfaction for fostering sustainable living.